Complemento nominal de substantivo e adjunto adnominal introduzido por preposição: uma análise baseada em corpus - Anya Karina Campos D'almeida e Pinho (2012)
The objective of the research that underpins this work is to investigate if the language in use confirms the patterns of behavior predicted by normative grammars for Nominal Complements of nouns (CN) and Adjunct adnominal started by preposition (AA). These works listed distinctive features of these two sentence terms, but by no means has the apprehension of such syntactic content become less painful for students and teachers. The results found point the sense that this difficulty emerges because of apprehension patterns that grammars try to impose the language through examples out of context, pinched of literary classics, no warranted by language remain in use. None of the behavioral patterns listed by grammars searched for CN and AA is completely confirmed by the language in use, being that most of them are totally refuted by it. Thus, as in many other studies previous to this, there was the need for suitability to the rules of grammar in language use, dynamic and contextualized as shown in the daily lives of its users. It reached this conclusion through the use of computer systems of Corpus Linguistics, in which were entered and processed a corpus built especially for this work and the KEY corpus, of the Linguateca available on the Internet. The collected data were organized in tables and then analyzed, indicating that, in terms of CN and AA, much needs to be revised, including the need to divide itself into two distinct groups whose characteristics terms the whole time overlap.